The Influence of Financial Literacy and Financial Behavior on Student Investment Decisions In Surabaya In Investment Company Digital-Based - Nur Azizah Romadhani; Sri Handini (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Financialiterations as knowledge, skills, and beliefs that influence attitudes and behaviors to improve the quality of decision-making and financial management in order to achieve well-being. This study aims to determine the influence of financial literacy and financial behavior on student investment decisions in Surabaya in digital-based investment companies both partially and simultaneously. This research is a type of quantitative research using primary data. The population in this study is all students in Surabaya who invest in digital-based investment companies, the number of samples is 150 respondents with a sampling method of purposive sampling techniques where samples are taken with certain considerations, data collection techniques in the form of questionnaires. The primary data source is an online questionnaire distributed to respondents. This data analysis technique uses instrument tests, classical assumption tests, multiple linear regression analysis, F tests, t tests, and R2 determinant coefficient tests. The results of this study show that financial literacy has a partial effect on student investment decisions in Surabaya in digital-based investment companies, financial behavior has a partial effect on student investment decisions in Surabaya in digital-based investment companies, and Financial literacy and financial behavior simultaneously affect the investment decisions of students in Surabaya in digital-based investment companies.